Public sector budget: An overview / Zuhariah Husin - Husin, Zuhariah (2006)
The public sector budget, tabled in Parliament every year, plays an important role in resource allocation towards achieving some public values. The importance of the budget is further stressed by the legal requirements for the preparation of budget. The main components in the budget are revenues and expenditure and presently every two years public sector entities have to go through the budget process, which starts in January and ends in December. A number of budget issues such as program evaluation, problem of shortfall, two-year budget and budget deficits seem to attract continuous debates and discussion amongst the concerned parties